Prevalence Of Secondary Caries In Children- Aretrospective Study - A, SWETAA.; P, JESSY (The journal of contemporary issues in business and government, 2021)
Background- Secondary caries develop perpendicular to the tooth surface and can be considered a primary lesion developing next to a restoration, and the wall lesions.Dental caries is the localised destruction of susceptible dental hard tissues by acidic byproducts from the bacterial fermentation of dietary carbohydrates. Aim- To assess the secondary caries prevalence and its approach in children . Results- The results prove that composite restoration has more prevalence of secondary caries which is about 69% and the most common class 2 restoration was affected which is about 79%.There is no statistical significant difference between the duration of the restoration and the material used (p>0.05). Conclusion- Within the limits of the study, it can be concluded that secondary caries were commonly noticed in patients with composite restoration. There is no association between duration of restoration and material used for restoration.